2011
DOI: 10.3122/jabfm.2011.03.110009
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Infections after a Routine Pelvic Exam

Abstract: Purpose: To determine if genitourinary problems are more common in women in the first 1 to 2 months after a routine pelvic examination.Methods: This was a historical cohort study in 2 family medicine teaching clinics at an urban university. Participants included all women who received a Papanicolaou smear during calendar year 2006. Subjects included all participants for weeks 1 to 7 after their Papanicolaou smear. Controls were all participants in weeks 8 to 52 after their Papanicolaou smear. The independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Indwelling catheter and hospitalization: the most important risk factor for bacteriuria is the presence of a catheter 8 ; catheter-associated UTI is the most common nosocomial infection; hospitalized patients have a risk of 5% per day while an indwelling catheter is in place 8,9 Recent or frequent sexual intercourse 10,11 Recent spermicide use, particularly associated with increased risk of Staphylococcus saprophyticus UTI 10,12 History of previous UTI 10 Insertive anal intercourse 13 Lack of circumcision in men 13 Pelvic examinations and Pap smear 14 Urinary tract stent Intermittent bladder catheterization 8 Obstructive uropathy, including neurogenic bladder and nephrolithiasis Vesicoureteric reflux or other functional abnormalities Chemical or radiation injury of uroepithelium Recent urinary tract instrumentation 15 Polycystic renal disease 16 Renal transplantation Immunodeficiency or immunosuppression 15 MICROBIOLOGY Most UTIs are monomicrobial; the most common pathogen is Escherichia coli, accounting for 70% to 95% cases of acute uncomplicated cystitis. 5,17 The second most common pathogen is Staphylococcus saprophyticus, accounting for 5% to 15% of UTIs, and occurs mainly in young women.…”
Section: Risk Factors For Utimentioning
confidence: 99%
“…Indwelling catheter and hospitalization: the most important risk factor for bacteriuria is the presence of a catheter 8 ; catheter-associated UTI is the most common nosocomial infection; hospitalized patients have a risk of 5% per day while an indwelling catheter is in place 8,9 Recent or frequent sexual intercourse 10,11 Recent spermicide use, particularly associated with increased risk of Staphylococcus saprophyticus UTI 10,12 History of previous UTI 10 Insertive anal intercourse 13 Lack of circumcision in men 13 Pelvic examinations and Pap smear 14 Urinary tract stent Intermittent bladder catheterization 8 Obstructive uropathy, including neurogenic bladder and nephrolithiasis Vesicoureteric reflux or other functional abnormalities Chemical or radiation injury of uroepithelium Recent urinary tract instrumentation 15 Polycystic renal disease 16 Renal transplantation Immunodeficiency or immunosuppression 15 MICROBIOLOGY Most UTIs are monomicrobial; the most common pathogen is Escherichia coli, accounting for 70% to 95% cases of acute uncomplicated cystitis. 5,17 The second most common pathogen is Staphylococcus saprophyticus, accounting for 5% to 15% of UTIs, and occurs mainly in young women.…”
Section: Risk Factors For Utimentioning
confidence: 99%
“…In a follow up study, 11 Tiemstra's group evaluated 1582 women who had Papanicolaou testing at any time and their rates of urinary tract infections (UTIs) during the next year. They found that within the first 7 weeks after a Papanicolaou test, UTIs occurred at a rate of 12.7 per 100 person years versus 6.51 per 100 person-years in the subsequent 45 weeks.…”
Section: Reading This Issue Of the Journal Of The Americanmentioning
confidence: 99%
“…Fear of pain and embarrassment were identified as barriers to cervical cancer screening in a recently published survey study from Brazil [55]. A specific potential harm was illustrated by a study reporting higher rates of urinary tract infection in the 7 weeks after a routine pelvic examination with cervical cancer screening [56].…”
Section: Is There a Role For The Annual Pelvic Examination In Asymptomentioning
confidence: 99%
“…Fear of pain and embarrassment were identified as barriers to cervical cancer screening in a recently published survey study from Brazil [55]. A specific potential harm was illustrated by a study reporting higher rates of urinary tract infection in the 7 weeks after a routine pelvic examination with cervical cancer screening [56].Another potential disservice of performing a pelvic examination in asymptomatic women is providing false reassurance to the provider and the patient regarding the absence of gynecologic malignancy. This was demonstrated by Padilla et al's studies in which even under the most seemingly ideal circumstance for accuracy (patients were under general anesthesia), the ability to identify ovarian masses was poor and identification of uterine size and contour was also limited [12,13].…”
mentioning
confidence: 99%